Base econômica e desenvolvimento local: estudo de caso múltiplo em municípios canavieiros - Montagnhani, Bruno Astolphi (2012)
This work has the purpose of compare and analyze the importance of the sugarcane industry like economic base, in job creation and local development in two cities, Mirandópolis-SP and Engenheiro Beltrão-PR. For this, was used the Economic Base Theory like a way to estimate the base employment and his multiplier effect over the not-base employment. The municipality of Mirandópolis makes part of Araçatuba s mesoregion, in São Paulo, and owns a population of 27.483 inhabitants. The municipality of Engenheiro Beltrão makes part of Parana s West-Central mesoregion, and the current population is 13.906 residents. Both municipalities have potentials that allow the specialization in the production of sugarcane s derivatives, being capable to create a surplus to exportation. In this way, the sugarcane agroindustry helps composing the economic base of the two cases under review. In the municipality located in São Paulo, in 2009, were created 3.447 formal employments, being 1.458 in the base sector (exportation) and 1.989 in the not-base sector (local market). The multiplier of calculated employment was about 2,36. In the same year, in Engenheiro Beltrão-PR were created 3.907 formal employments, being 2.017 in the base sector and 1.890 in the not-base sector. The multiplier of calculated employment was about 1,93. Thus, it is noted that the employment multiplier has a direct relation with the area size, in other words, the larger the municipality and the greater its resident population, larger will be the multiplier magnitude. The evolution of the indicators of local development also showed more favorable in Mirandópolis-SP, compared to Engenheiro Beltrão-PR: 1) in this first municipality, the process of population reduction was interrupted after the activities connected with the sugarcane agroindustry arrival, but the same didn t happen in the second municipality; 2) The Gross Domestic Product (GDP) of Mirandópolis-SP presented a trajectory of stability over the years, while that the GDP of Engenheiro Beltrão-PR is characterized by high volatility; 3) the service sector assumes a largest participation in the GDP of Mirandópolis, being this a characteristic of most developed economies; 4) the income concentration presents a reduction tendency in Mirandópolis-SP, in the other hand in Engenheiro Beltrão-PR the opposite is true; 5) the proportion of peolple considered poor in Mirandópolis-SP is smaller than in Engenheiro Beltrão; 6) the HDI-M of Mirandópolis-SP is higher than the HDI-M of Engenheiro Beltrão-PR. However, it is important to remember that the data should not be credited solely to the sugarcane agroindustry, should also consider the State s participation in this process through the adoption of social policies and local development.